Paroxysmal exercise‐induced dystonia within the phenotypic spectrum of ECHS1 deficiency. Issue 7 (19th April 2016) - Olgiati, Simone; Skorvanek, Matej; Quadri, Marialuisa; Minneboo, Michelle; Graafland, Josja; Breedveld, Guido J.; Bonte, Ramon; Ozgur, Zeliha; van den Hout, Mirjam C.G.N.; Schoonderwoerd, Kees; Verheijen, Frans W.; van IJcken, Wilfred F.J.; et al.
Abstract: Background: ECHS1 encodes a mitochondrial enzyme involved in the degradation of essential amino acids and fatty acids. Recently, ECHS1 mutations were shown to cause a new severe metabolic disorder presenting as Leigh or Leigh‐like syndromes. The objective of this study was to describe a family with 2 siblings affected by different dystonic disorders as a resulting phenotype of ECHS1 mutations. Methods: Clinical evaluation, MRI imaging, genome‐wide linkage, exome sequencing, urine metabolite profiling, and protein expression studies were performed. Results: The first sibling is 17 years old and presents with generalized dystonia and severe bilateral pallidal MRI lesions after 1 episode of infantile subacute metabolic encephalopathy (Leigh‐like syndrome). In contrast, the younger sibling (15 years old) only suffers from paroxysmal exercise‐induced dystonia and has very mild pallidal MRI abnormalities. Both patients carry compound heterozygous ECHS1 mutations: c.232G>T (predicted protein effect: p.Glu78Ter) and c.518C>T (p.Ala173Val). Linkage analysis, exome sequencing, cosegregation, expression studies, and metabolite profiling support the pathogenicity of these mutations. Expression studies in patients' fibroblasts showed mitochondrial localization and severely reduced levels of ECHS1 protein. Increased urinary S‐(2‐carboxypropyl)cysteine and N‐acetyl‐S‐(2‐carboxypropyl)cysteine levels, proposed metabolic markers of this disorder, were documented in both siblings. Sequencing ECHS1 in 30 unrelated patients with paroxysmal dyskinesias revealed no further mutations. Conclusions: The phenotype associated with ECHS1 mutations might be milder than reported earlier, compatible with prolonged survival, and also includes isolated paroxysmal exercise‐induced dystonia. ECHS1 screening should be considered in patients with otherwise unexplained paroxysmal exercise‐induced dystonia, in addition to those with Leigh and Leigh‐like syndromes. Diet regimens and detoxifying agents represent potential therapeutic strategies. © 2016 International Parkinson and Movement Disorder Society